2014
DOI: 10.1016/j.pmrj.2013.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Uterine Bleeding in a Postmenopausal Woman After an Intra‐articular Knee Injection With Triamcinolone: A Case Report

Abstract: A 71-year-old postmenopausal woman was referred for evaluation of pain in her left knee. She was previously treated with oral analgesics, but her knee pain persisted, limiting her functional mobility. An intra-articular corticosteroid injection of the left knee was administered. Several days after the injection, she reported vaginal bleeding that resolved spontaneously after 5 days. We postulate that exogenous steroids disrupted circulating hormone levels, leading to abnormal postmenopausal uterine bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In the literature, there are only a few reports regarding over-bleeding after steroid injections (3,6,9,11,15). In 2002, Manchikanti reported that exogenous steroids suppress the hypothalamic-pituitary-adrenal (HPA) axis (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there are only a few reports regarding over-bleeding after steroid injections (3,6,9,11,15). In 2002, Manchikanti reported that exogenous steroids suppress the hypothalamic-pituitary-adrenal (HPA) axis (11).…”
mentioning
confidence: 99%
“…In addition, Lamberts et al found that recovery of the HPA axis may take as long as one year after exogenous steroid discontinuation (9). James et al reported abnormal uterine bleeding after corticosteroid administration via an intra-articular knee injection and concluded that the exogenous steroids disrupted circulating hormone levels, leading to abnormal bleeding (6). In 1999, Ullian described the effects of steroids on vascular tone and emphasized that steroids increase vascular tone by trophic effects including hypertrophy and/or hyperplasia of vascular smooth muscle cells (15).…”
mentioning
confidence: 99%